Adoption of renewable energy innovations among hoteliers in Portugal - Silva,Luís (2022)
Abstract This article examines the owners' and/or managers' perceptions and attitudes towards the adoption of renewable energy innovations in hotels in Portugal, as well as the factors that affect the adoption. The study is based on an e-mail-based survey conducted with hoteliers in 2022 (n = 208). First, the results demonstrate that despite the respondents' positive perceptions of renewable energy, the adoption level of renewable energy innovations in hotels is low. Second, the reasons given for this gap relate mainly to unfavourable market factors. Third, market factors have a statistically significant influence on adoption. In contrast, the characteristics of the hotels and hoteliers, their opinion about the need to cut the carbon footprint of tourist accommodations and the type of hotel ownership have no significant influence.